2001
DOI: 10.1053/joca.2001.0433
|View full text |Cite
|
Sign up to set email alerts
|

Guidance by ultrasound of intra-articular injections in the knee and hip joints

Abstract: By the injection of air, it is possible to test the placement of intraarticular injections in both hip and knee joints. This procedure will give a supplementary documentation of the injection as compared to a mere ultrasonographic demonstration of the position of the needle in the joint. The method is proposed as a tool for both learning purposes and quality assurance in daily therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(115 citation statements)
references
References 14 publications
3
106
0
6
Order By: Relevance
“…Although a previous study showed the feasibility of using sonography to guide intra-articular injections in the knee, 10 a need exists to further show its advantages, such as the accuracy rate and operability. Driven by a need for more accurate, safer, and less costly methods for intraarticular injections, this study was undertaken to investigate the feasibility of using real-time highresolution sonography to guide an injection needle into the intra-articular space within the knee.…”
mentioning
confidence: 99%
“…Although a previous study showed the feasibility of using sonography to guide intra-articular injections in the knee, 10 a need exists to further show its advantages, such as the accuracy rate and operability. Driven by a need for more accurate, safer, and less costly methods for intraarticular injections, this study was undertaken to investigate the feasibility of using real-time highresolution sonography to guide an injection needle into the intra-articular space within the knee.…”
mentioning
confidence: 99%
“…All the trials have shown a reduction of pain, which, in general, becomes evident within 3 months and persists in the following months. Only few studies report a precocious reduction of the pain : within a week, according to Brocq (Brocq et al, 2002) (-27 %), and within the first 2 -4 weeks according to Qvistgaard (Qvistgaard et al, 2001) (-14 % and -32 %, respectively). The positive effects on pain after 1 -3 months range from -16.1 % to -52.2 % (mean -37.2 %), whereas, overall, the mean Visual Analogic Scale score decreases about 49 % after 3 -6 months (range 31 -80 %) (Abate et al, 2008).…”
Section: Hip Osteoarthritismentioning
confidence: 99%
“…The anterior (superior collicular recess) and the supero-anterior recesses are the most important in musculoskeletal ultrasound assessment because of the sensitivity in depicting synovitis. (Backhaus M et al, 2001;Iagnocco A et al, 2006;Qvistgaard E et al, 2001 …”
Section: Sonoanatomy Patient Position and Scanning Techniquementioning
confidence: 99%
“…Ultrasonography has a very important advantage over other imaging methods because it allows the concomitant visualization of the target structure, the needle penetration and tip positioning as well as the drug deposition (Bradley MJ, 2001). Indeed, musculoskeletal ultrasound evaluation is an accurate and reliable method in depicting articular and periarticular lesions, has no radiation, is cheap and quick to perform and allows repeated examinations at baseline and during follow up (Bierma-Zeinstra et al, 2001;Koski JM et al, 1989;Iagnocco A et al, 2006;Qvistgaard E et al, 2001). Moreover, a modular flexible training strategy to achieve competence in diagnostic as well as in interventional musculoskeletal ultrasound showed a fast learning curve among rheumatologists, thus encouraging its employment in daily practice (Atchia I et al, 2007).…”
Section: Introductionmentioning
confidence: 99%